Governance in the Patrimonial State: reference to the venezuelan case (Revista Científica Compendium, 2019)
In this essay, fundamental milestones of the scientific and social institutionalization of Medicine in Barquisimeto in the period between 1870 and 1980 are addressed, giving emphasis to the foundation of the Charity Hospital (1877) and its relation to the origins of the medical studies in the region. The role of physicians Luis Razetti and Antonio Maria Pineda stands out in the times of the first local hospital in the XIX century and the creation of the First-Category School of Barquisimeto by the National Executive, in which university certificates in Medicine are authorized to be awarded. Once, it was closed in 1904, the medical knowledge does not disappear, but opens its path towards the Medicine and Surgery Society as well as the organizational and administrative progress of Antonio Maria Pineda Hospital created in1954. The impetus given by the Society of Friends of Barquisimeto, civil society, the political, religious, and economic powers made it possible that on September 22, 1962, the national Government created the Experimental Center of Superior Studies (CEDES), where the academic and administrative structure of the university training of physicians will be formalized until 1969 with the founding of the Experimental University of the Central-Western Region (URCO). Indicators of institutionalization, academic formation and social organization as an agency for the development of medical studies in Barquisimeto are analyzed with the method of the social history and documentary critique. The sources come from the regional historiography and Scientific Bulletin from the Charity Hospital (1877-1918). As a conclusion, we support the relevance of the participation of local society and leadership of the doctors in the scientific and social institutionalization of the medicine for the urban development of the region, both the period 1877-1954 and the period 1962-1980
Keywords: Charity Hospital; Antonio Maria Pineda Hospital; Medical School; university studies; Barquisimeto